2008
DOI: 10.1016/j.jacl.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Getting the word out: Teaching middle-school children about cardiovascular disease

Abstract: Cardiovascular disease (CVD) has roots in childhood; since CVD begins early, a clear strong case for early education focused on CVD primary prevention exists. Scientists are not traditionally involved in disseminating health knowledge into public education. Similarly, public school teachers typically do not have access to biomedical research that may increase their students' health science literacy. One way to bridge the 'cultural' gap between researchers and school teachers is to form science education partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…demonstrated that integration of National Heart, Lung, and Blood Institute research findings into curriculum coincides with education levels. 30 , 31 Programs such as the targeted earlier intervention curriculum may therefore be an effective way to introduce CVD-specific knowledge, such as the ethnicity risk factor, to newer generations of Chinese Canadians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that integration of National Heart, Lung, and Blood Institute research findings into curriculum coincides with education levels. 30 , 31 Programs such as the targeted earlier intervention curriculum may therefore be an effective way to introduce CVD-specific knowledge, such as the ethnicity risk factor, to newer generations of Chinese Canadians.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent publication by Lam & Chu has found that the prevalence of type 2 diabetes was higher in Chinese Canadian adults with ischemic stroke. 30 What this may all suggest is that over time as ethnic Chinese…”
Section: Awareness Of Chinese Ethnicity As a Risk Factormentioning
confidence: 99%
“…We examined this age group because adolescence is an important developmental period during which young people gain autonomy and greater personal control over their health-related behaviors (Brown, Teufel, & Birch, 2007;Toepperwein, Pruski, Blalock, Lemelle, & Lichtenstein, 2008). It is also a period of many physical, social, emotional, and educational changes that can be difficult to navigate and may contribute to impediments in psychosocial well being.…”
Section: Discussionmentioning
confidence: 99%